2020
DOI: 10.2147/dddt.s268524
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Impact of Icariside II on Human Prostate Cancer Cell Proliferation, Mobility, and Autophagy via PI3K-AKT-mTOR Signaling Pathway</p>

Abstract: The flavonol glycoside icariside II (ICA II) has been shown to exhibit a range of anti-tumor properties. Herein, we evaluated the impact of ICA II on human prostate cancer cell proliferation, motility, and autophagy, and we further evaluated the molecular mechanisms underlying these effects. Methods: We treated DU145 human prostate cancer cells with a range of ICA II doses and then assessed their proliferation via CCK-8 assay, while flow cytometry was used to monitor apoptosis and cell cycle progression. We fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In human esophageal squamous carcinoma Eca109 cells, Icariside II was demonstrated to be highly effective in downregulating β-catenin and cyclin D1 protein expression and stochastically inducing cell cycle arrest (Wang et al, 2011). The cell cycle blockage in human PC-3 and DU145 prostate cancer cells at the G0/G1 checkpoint was caused by Icariside II in a dose-dependent manner, which increased the percentage of cells undergoing G1 phase cell cycle arrest to 45.7-80% upon treatment with 40 µM (Lee et al, 2009;Li et al, 2020). These results were supported in a study by Wei Z, which showed that Icariside II induced significant accumulation of cells at the G1/G0 phase with decreased cell populations at the S phase and the G2/M phase in cervical cancer (Sun et al, 2020).…”
Section: Cell Cycle Arrestmentioning
confidence: 98%
See 2 more Smart Citations
“…In human esophageal squamous carcinoma Eca109 cells, Icariside II was demonstrated to be highly effective in downregulating β-catenin and cyclin D1 protein expression and stochastically inducing cell cycle arrest (Wang et al, 2011). The cell cycle blockage in human PC-3 and DU145 prostate cancer cells at the G0/G1 checkpoint was caused by Icariside II in a dose-dependent manner, which increased the percentage of cells undergoing G1 phase cell cycle arrest to 45.7-80% upon treatment with 40 µM (Lee et al, 2009;Li et al, 2020). These results were supported in a study by Wei Z, which showed that Icariside II induced significant accumulation of cells at the G1/G0 phase with decreased cell populations at the S phase and the G2/M phase in cervical cancer (Sun et al, 2020).…”
Section: Cell Cycle Arrestmentioning
confidence: 98%
“…Icariside II, as a novel phosphodiesterase 5 inhibitor, was found to play a role in regulating autophagy via the PI3K/AKT/ mTOR, ROS/GSK-3β/mitochondrial, and PKG/GSK-3β signaling pathways in different diseases (Gao et al, 2017;Gao et al, 2020;Li et al, 2020;Zhang et al, 2020). In human prostate cancer, autophagy induced by Icariside II was characterized by enhanced autophagosome formation, reduction in P70S6K expression, and upregulation of LC3 and Beclin-1 by inhibiting PI3K-AKT-mTOR activity (Li et al, 2020). Till date, the influence of Icariside II on autophagy in different cancer cell lines is not well elucidated and more studies are needed to shed better light on this subject.…”
Section: Autophagy Triggeringmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the TCM, Jixuepaidu Tang-1, and Astragaloside IV have also been confirmed to be involved in the process of liver cancer and kidney injury by regulating ATB ( Li et al, 2018 ) and LOC498759 ( Jin et al, 2019 ), respectively. It was known that the treatment of flavanol glycoside icaridin, the active ingredient of TCM, could inhibit the proliferation and migration of human PCa cells and enhance autophagy by regulating the PI3K/AKT/mTOR signaling pathway ( Li S. et al, 2020 ). However, the effects of the A–S drug pair on the PI3K pathway, autophagy, and lncRNAs have never been studied in PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Herba Epimedii (commonly named as Yin-yang-huo in China) is a traditional herb or health food that is widely used in China for the prevention and treatment of various diseases. In vivo and in vitro studies have been conducted over the past few decades and found that ICS II can treat a variety of cancers including acute myeloid leukemia [ 15 ], prostate cancer [ 16 ], cervical cancer [ 17 ], etc. It has also been used to treat myocardial ischemic and reperfusion injury [ 18 , 19 ], ED [ 20 , 21 ] and many neurological disorders such as Alzheimer's disease [ 22 24 ], vascular dementia [ 25 ], and subarachnoid hemorrhage [ 26 ].…”
Section: Introductionmentioning
confidence: 99%